The activity of N-acetyl-β-D-hexosaminidase in serum and urine of patients with pancreatic cancer - Szajda, Sławomir Dariusz; Snarska, Jadwiga; Kamiński, Fabian; Siedlecka, Katarzyna; Waszkiewicz, Napoleon; Knaś, Małgorzata; Zwierz, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2006)
Background: N-acetyl-β-D-hexosaminidase (HEX) is lysosomal exoglycosidase (EC 3.2.1.52), which releases N-acetyloheksozoamines from non reducing ends of oligosaccharide chains of glycoconjungates (glycoproteins, glycolipids and proteoglycans). Determination of HEX activity in tissues and body fluids was applied in diagnostics of Tay-Sachs and Sandhoff’s, as well as, kidney and liver diseases. The aim of our work was to evaluate the activity of HEX in blood serum and urine of patients with pancreatic cancer, as a potential cancer marker. Material and methods: Blood and serum were taken from 7 patients (44-77 years old) with histopathologically confirmed adenocarcinoma of the pancreas, in I Department of General and Endocrinological Surgery, Medical University, Białystok, Poland, and 8 (22-31 years old) healthy volunteers. The activity of HEX was determined by Chatterjee et al method as modified by Zwierz et al. Amount of p-nitrophenol released from p-nitrophenyl-β-D-N-acetylglucosaminepyranoside (Sigma) was evaluated on microplate reader EL X 800, BIO-TEK at 410 nm. The concentration of HEX activity was expressed in pKat/mL, and specific activity in pKat/mg protein. Protein in serum was determined by the biuret, and in urine by the Lowry method. Results: Concentration and specific of the HEX activity in serum of patients with pancreatic cancer were more than three limes higher than concentration and specific of HEX activity in serum of healthy persons (p<0.02). Specific activity of HEX in urine of patients with pancreatic cancer was more than twice higher, than concentration of HEX in urine of healthy persons (p<0.02). Conclusions: Our results suggest possibility of the determination of the HEX activity in serum and urine as a marker of pancreatic cancer.